Assessment of predominant noise sources and workers exposure in downstream oil and petrochemical industries in Malaysia / Aliff Firdaus Mat Yusoff - Aliff Firdaus, Mat Yusoff (2018)
Abundant of publicly available data supports the fact that noise induced hearing loss (NIHL) is one of major threat to workers’ health in most industries globally. Similar trending can be observed domestically, where NIHL remains as the most reported occupational health diseases since the last decade. FMA (Noise exposure) Regulations, 1989 is currently undergoing revision process. The revised noise regulation is expected to be more stringent and putting emphasizes on noise control at the source rather than relying only on hearing protection device to protect workers’ hearing. In addition, the regulations will also introduce periodic noise monitoring and more significant penalty will be enforced. As the regulations on noise becoming more stringent, a comprehensive and pragmatic approach need to be adopted by the industry to meet the requirements. This study aims to provide insight on the current exposure level, compliance status and characterizing noise sources within oil and gas industries. The samples for this study were collected from noise exposure monitoring report of the facilities in the respective business sectors within oil and gas industries, namely upstream, downstream, midstream and petrochemical. Statistical analysis was performed on parameters used to evaluate workers’ exposure and compliance, LAeq8, Lmax and Lpeak. The analysis was performed to characterize the noise exposure level with respect to their business, facilities and their job functions. The mean LAeq8 for oil and gas industries was 76.3 dB(A) (95% CI = 76.3 – 78.0). Therefore, the study concluded that overall oil and gas industries is in compliance with the existing LAeq8 noise limit of 90 dB(A) and revised noise limit of 85 dB(A). However, the study predicted with 95% probability that, 10% of the workers’ exposure may still exceed 90 dB(A). The data suggested that upstream business, specifically exploration and production facilities, may face challenges in complying to the revised noise exposure limit. Average Lmax was 107.1 dB(A) (95% CI = 106.3 – 108.0), hence, the oil and gas industries in general was in compliance to Lmax limit of 115 dB(A). As for exposure to ceiling limit, the mean Lpeak was 136.3 dB (95% CI = 136.0 – 137.0). All other business categories except for Downstream were in compliance to Lpeak PEL of 140 dB. AIHA noise exposure control category protocol was adopted to conclude Daily Noise Dose (DND). Approximately 86% of the samples were concluded as Rating 3 (50% - 100% DND) or below, 11% at Rating 4 (> 100% DND) and 3% at Rating 5 (> 500% DND). Upstream business contributed to the highest proportion of working cluster assigned as Rating 4 (61%) or Rating 5 (77%). Learnings from this study hopefully will provide facilitate the authorities, and industry in the implementation of revised noise regulation. This study recommends that company should consider more robust approach such as adopting Buy-Quiet policy or Quiet-by-Design to eliminate or minimize noise at the source. This will prevent over-reliance on HPD to protect our workers’ precious hearing. Keywords: Noise sources; noise exposure; noise regulations; noise limit; oil and gas